(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
This article reviews the master’s research in Design, developed between 2005 and 2006, which focused on a group of embroiderers from the Barateiro Community (Itapajé – State of Ceará). The embroidery produced there was based on the forget-me-not flowers and strawberry fruits (separated or combined), very common in that municipality. Based on the diagnosis carried out to identify problems in relation to the production, circulation and distribution of embroidery produced in Barateiro (Itapajé – State of Ceará), the Municipal Department of Education developed and implemented “Programa de Revitalização do Artesanato de Itapajé” (Itapajé Handicraft Revitalization Program – PRA-ITA), promoting an intervention with the embroiderers regarding the embroidery pattern that became stylized representations of the flamboyant flower. This action, carried out under the aegis of design, made it possible to configure a collective signature on the embroidery produced in that community. The research’s main objective was to demonstrate this process and how aesthetic intervention has become a cultural marker.